Pengabaian Scott Morrison terhadap Komitmen Bali Process pada Isu Penanganan Pengungsi - Isnindya Ramadhani Mamissa Putri (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
The Asia-Pacific region faces complex refugee challenges, particularly after the 2015 Andaman Sea crisis. In response, the Bali Process adopted the 2016 Bali Declaration, which emphasized protection-sensitive approaches, respect for non-refoulement, and regional cooperation in refugee management. However, Australia’s role as co-chair of the Bali Process became increasingly problematic under Prime Minister Scott Morrison from 2018 to 2022, as his administration adopted restrictive policies toward immigrants, asylum seekers, and refugees. This research aims to explain why Australia under Morrison neglected its Bali Process commitments in refugee protection and management. Using an actor-specific approach in Foreign Policy Analysis, this study employs a qualitative interpretive method with discourse analysis of Morrison’s public statements, policy responses, official documents, and secondary literature. The findings show that Morrison’s security-oriented problem representation, motivation to maintain domestic political support, and emotional distance from refugee protection contributed to Australia’s neglect of the Bali Declaration. This research contributes to Foreign Policy Analysis by showing how leaders’ perceptions, motivations, and emotions shape state behavior toward regional humanitarian commitments, while also offering practical insights into the domestic political constraints on refugee protection